Solve the equation for b.

-4(b + 3) + b(b - 3) = -b(6 - b) + 2(b - 3)

-4(b + 3) + b(b - 3) = -b(6 - b) + 2(b - 3)

-4b - 12 + b² - 3b = -6b + b² + 2b - 6 {used distributive property}

b² - 7b - 12 = b² - 4b - 6 {combined like terms}

-7b - 12 = -4b - 6 {subtracted b² from each side}

-3b - 12 = -6 {added 4b to each side}

-3b = 6 {added 12 to each side}

b² - 7b - 12 = b² - 4b - 6 {combined like terms}

-7b - 12 = -4b - 6 {subtracted b² from each side}

-3b - 12 = -6 {added 4b to each side}

-3b = 6 {added 12 to each side}

**b = -2**{divided each side by -3}*- Algebra House*